2020
DOI: 10.3390/ijms21020557
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Contributes to Indomethacin-Induced Glioma Apoptosis

Abstract: The dormancy of cellular apoptotic machinery has been highlighted as a crucial factor in therapeutic resistance, recurrence, and poor prognosis in patients with malignancy, such as malignant glioma. Increasing evidence indicates that nonsteroidal anti-inflammatory drugs (NSAIDs) confer chemopreventive effects, and indomethacin has been shown to have a novel chemotherapeutic application targeting glioma cells. To extend these findings, herein, we studied the underlying mechanisms of apoptosis activation caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…The amplification of apoptosis and the overall antitumor effect of both COX-1 and COX-2 inhibitors have been repeatedly described for a variety of transformed cells. For example, a non-selective COX inhibitor used in this study, indomethacin, suppressed the growth of human colon adenocarcinoma cells [15], MNNG/HOS osteosarcoma cells [16], human H4 and U87 glioma cells [17], and many other cell lines. The proapoptotic effect of COX inhibitors is associated with both reduced COX catalytic activity and inhibition of PGE2 synthesis, even with COX-independent mechanisms [18,19].…”
Section: Discussionmentioning
confidence: 91%
“…The amplification of apoptosis and the overall antitumor effect of both COX-1 and COX-2 inhibitors have been repeatedly described for a variety of transformed cells. For example, a non-selective COX inhibitor used in this study, indomethacin, suppressed the growth of human colon adenocarcinoma cells [15], MNNG/HOS osteosarcoma cells [16], human H4 and U87 glioma cells [17], and many other cell lines. The proapoptotic effect of COX inhibitors is associated with both reduced COX catalytic activity and inhibition of PGE2 synthesis, even with COX-independent mechanisms [18,19].…”
Section: Discussionmentioning
confidence: 91%
“…The levels of Mcl-1 and Noxa are regulated at several steps, particularly the transcriptional level [ 27 , 45 , 46 ]. ER stress represents a crucial upstream regulator of the transcription of the Bcl-2 family proteins, either promoting or inhibiting transcription [ 41 , 47 ]. Under stressed situations, the physiological role of ER stress is to restore the organelle’s homeostasis; however, sustained or chronic ER stress can trigger the cell death program via a complex series of biochemical events involving protein phosphorylation and transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of cell death, reduction of cell proliferation and motility is found in aspirin-treated glioblastoma cancer stem cells [ 53 ]. Previously, we reported the role of an apoptotic axis triggered by ER stress, which led to p38 activation and Akt inactivation, resulting in Mcl-1 and FLIP downregulation in indomethacin-treated glioma cells [ 47 ]. The maintenance of ER homeostasis helps to suppress ER stress-induced apoptotic cell death in malignant glioma [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1,24,25 ] Activation of ER stress signalling PERK/eIF‐2α/ATF‐4/CHOP and/or IRE‐1α/JNK1/2 pathways by indomethacin and diclofenac results in apoptosis in several culture models including primary pig gastric epithelial cells, Huh‐7, H‐4 and U‐87 cells. [ 4,5 ] In this study, we demonstrated that indomethacin and diclofenac caused ER stress‐mediated apoptosis in Caco‐2 cells by activating different arms of ER sensors. These two NSAIDs and the other two known ER stressors tunicamycin and thapsigargin shared a similar apoptosis‐inducing mechanism by activation of PERK/eIF‐2α/ATF‐4/CHOP pathway.…”
Section: Discussionmentioning
confidence: 78%
“…[ 3 ] Indomethacin and diclofenac have been linked to increased phosphorylation of ER sensors, particularly pancreatic‐like ER kinase (PERK) and inositol‐requiring enzymes‐1α (IRE‐1α), in various cell models such as human glioma cells. [ 4,5 ] Activation of PERK upregulates the C/EBP homologous transcription factor expression (CHOP), resulting in alteration of apoptotic proteins, mitochondrial dysfunction and apoptosis. [ 6,7 ]…”
Section: Introductionmentioning
confidence: 99%